A phase III, multi-arm multi-stage covariate-adjusted response-adaptive randomized trial to determine optimal early mobility training after stroke (AVERT DOSE) - Julie Bernhardt; Leonid Churilov; Helen Dewey; Geoffrey Donnan; Fiona Ellery; Coralie English; Lan Gao; Kathryn Hayward; Frances Horgan; Bent Indredavik; Hannah Johns; Peter Langhorne; et al. (SAGE Journals, 2023)
Rationale:
The evidence base for acute post-stroke rehabilitation is inadequate and global guideline recommendations vary.
Aim:
To define optimal early mobility intervention regimens for ischemic stroke patients of mild and moderate severity.
Hypotheses:
Compared with a prespecified reference arm, the optimal dose regimen(s) will result in more participants experiencing little or no disability (mRS 0–2) at 3 months post-stroke (primary), fewer deaths at 3 months, fewer and less severe complications during the intervention period, faster recovery of unassisted walking, and better quality of life at 3 months (secondary). We also hypothesize that these regimens will be more cost-effective.
Sample size estimates:
For the primary outcome, recruitment of 1300 mild and 1400 moderate participants will yield 80% power to detect a 10% risk difference.
Methods and design:
Multi-arm multi-stage covariate-adjusted response-adaptive randomized trial of mobility training commenced within 48 h of stroke in mild (NIHSS < 7) and moderate (NIHSS 8–16) stroke patient strata, with analysis of blinded outcomes at 3 (primary) and 6 months. Eligibility criteria are broad, while excluding those with severe premorbid disability (mRS > 2) and hemorrhagic stroke. With four arms per stratum (reference arm retained throughout), only the single treatment arm demonstrating the highest proportion of favorable outcomes at the first stage will proceed to the second stage in each stratum, resulting in a final comparison with the reference arm. Three prognostic covariates of age, geographic region and reperfusion interventions, as well as previously observed mRS 0–2 responses inform the adaptive randomization procedure. Participants randomized receive prespecified mobility training regimens (functional task-specific), provided by physiotherapists/nurses until discharge or 14 days. Interventions replace usual mobility training. Fifty hospitals in seven countries (Australia, Malaysia, United Kingdom, Ireland, India, Brazil, Singapore) are expected to participate.
Summary:
Our novel adaptive trial design will evaluate a wider variety of mobility regimes than a traditional two-arm design. The data-driven adaptions during the trial will enable a more efficient evaluation to determine the optimal early mobility intervention for patients with mild and moderate ischemic stroke.
Keywords: Cardiology; Medicine; 110904 Neurology and Neuromuscular Diseases